Learning Clinic: Designing Problem Based Learning Student Worksheets - Monika Handayani; Andayani Andayani; Jaka Warsihna (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
In line with the implementation of the 2013 curriculum and High Order Thinking Skills (HOTS), teachers are expected to be able to design teaching materials that can facilitate critical thinking learners through investigation activities. LKPD (Lembar Kerja Peserta Didik) based on Problem Based Learning (PBL) is one way that can encourage learners to think critically and creatively to complete learning activities that occur in everyday life. The purpose of this community service activity, teachers can design LKPD based on the PBL model and apply it in learning activities. The products resulting from activities to this community are LKPD based on the PBL model. The materials used are examples of LKPD based on the PBL model and materials on steps in PBL activities that can be aligned with the material in the 2013 curriculum. The method used is the socialization of community service and implementation activities in their respective teacher classes. The result of community service activities is LKPD based on the PBL model products made by teachers and the ease of teachers in construct LKPD based on the PBL model with learning activities to be carried out. In the conclusion of this community service activity, teachers need socialization and assistance in making teaching materials such as LKPD based on the PBL model to facilitate teachers in conducting learning activities.